Analysis of nucleotide diphosphate sugar dehydrogenases reveals family and group‐specific relationships. Issue 1 (11th January 2016) - Freas, Nicholas; Newton, Peter; Perozich, John
Abstract : UDP‐glucose dehydrogenase (UDPGDH), UDP‐ N ‐acetyl‐mannosamine dehydrogenase (UDPNAMDH) and GDP‐mannose dehydrogenase (GDPMDH) belong to a family of NAD + ‐linked 4‐electron‐transfering oxidoreductases called nucleotide diphosphate sugar dehydrogenases (NDP‐SDHs). UDPGDH is an enzyme responsible for converting UDP‐d ‐glucose to UDP‐d ‐glucuronic acid, a product that has different roles depending on the organism in which it is found. UDPNAMDH and GDPMDH convert UDP‐ N ‐acetyl‐mannosamine to UDP‐ N ‐acetyl‐mannosaminuronic acid and GDP‐mannose to GDP‐mannuronic acid, respectively, by a similar mechanism to UDPGDH. Their products are used as essential building blocks for the exopolysaccharides found in organisms like Pseudomonas aeruginosa and Staphylococcus aureus . Few studies have investigated the relationships between these enzymes. This study reveals the relationships between the three enzymes by analysing 229 amino acid sequences. Eighteen invariant and several other highly conserved residues were identified, each serving critical roles in maintaining enzyme structure, coenzyme binding or catalytic function. Also, 10 conserved motifs that included most of the conserved residues were identified and their roles proposed. A phylogenetic tree demonstrated relationships between each group and verified group assignment. Finally, group entropy analysis identified novel conservations unique to each NDP‐SDH group, including residue positions critical to NDP‐sugar substrate interaction, enzyme structure and intersubunit contact. These positions may serve as targets for future research. Enzymes: UDP‐glucose dehydrogenase (UDPGDH, EC 1.1.1.22 ).